Smoking behaviour and its influencing factors among adult population in selected communities of rural Bangladesh - Islam, Kazi R.; Rume, M. I. R.; Roy, Liton; Rahman, Shahnaz; Rahman, M. S. (International Journal Of Community Medicine And Public Health, 2021)
Background: Tobacco is a leading cause of preventable mortality and morbidity in the majority of high-income countries, and it is becoming increasingly prevalent in low-income countries. This study aims to assess the smoking behavior among adult population in a selected community of Mymensing district. Methods: This descriptive type of cross sectional study was conducted to assess the smoking behavior among the adult population in a selected community of Mymensing district. The study period was four months starting from June 2018 to September 2018. One hundred and eighty two (182) people were selected considering the inclusion and exclusion criteria. The study taken informed written consent from all the participants. All the data were entered and analyzed by using statistical packages for social science (SPSS) software version 16.0 (Chicago). Results: This study revealed that the highest 53.3% of the respondents were smoking daily 11-15 cigarette/day. The highest 45.6% of the respondents were smoking for 6-10 years. 52.2% of the respondents were thinking depression influence on smoking. 66.5% of the respondents were thinking personal life problem influence on smoking. 42% start and continue smoking due to friends followed by 27% were due to stress and anxiety, 12% were for relaxation, 10% were personal life problem and 4% were start and continue smoke for pleasure and fun. Conclusions: It was observed that all of the respondents have given positive comment about the influence of television (TV)/media on cessation of tobacco use.